2016
DOI: 10.1038/aps.2015.128
|View full text |Cite
|
Sign up to set email alerts
|

Insulin deficiency induces rat renal mesangial cell dysfunction via activation of IGF-1/IGF-1R pathway

Abstract: Aim: Diabetic nephropathy is one of the major complications of diabetes and the major cause of end-stage renal disease. In this study we investigated the insulin deficiency (ID) induced changes in renal mesangial cells (MCs) and in the kidney of STZ-induced diabetic rats. Methods: Cultured rat renal MCs were incubated in ID media. Cell proliferation was analyzed using BrdU incorporation assay. The expression of insulin receptor (IR), insulin-like growth factor-1 receptor (IGF-1R), phosphorylated IGF-1R, fibron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Diabetic dyslipidemia has been shown to be associated with the development of cardiovascular disease and kidney dysfunction [22] . Studies have revealed that dyslipidemia might contribute to the progression of DN via Toll-like receptor 4 signaling, the renin-angiotensin system, transforming growth factor-β signaling, and oxidative stress [23][24][25][26] . Ruan et al proposed that inflammatory stress plays an important role in contributing to ectopic lipid accumulation [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic dyslipidemia has been shown to be associated with the development of cardiovascular disease and kidney dysfunction [22] . Studies have revealed that dyslipidemia might contribute to the progression of DN via Toll-like receptor 4 signaling, the renin-angiotensin system, transforming growth factor-β signaling, and oxidative stress [23][24][25][26] . Ruan et al proposed that inflammatory stress plays an important role in contributing to ectopic lipid accumulation [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence uncovered that miR-NAs modulated the aerobic glycolysis via targeting the enzymes involved in glycolysis such as GLUT1, G6PD and LDHA [30][31][32][33]. IGF-1R is a transmembrane protein with tyrosine kinase activity belonging to the insulin receptor family [34][35][36]. Up-regulation of IGF-1R has been observed in several cancers, including HCC and renal cell carcinoma [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The procedures were performed as described previously. 47 Amplification was performed using the following primers: 5 0 -TCATCTTGGCAGTT CTCGCA-3 0 (forward) and 5 0 -TCTTCTTGAGGTGGTCGGAC-3 0 (reverse) for mouse ITGAV, 5 0 -GGCACAAAGACCGTTGA-3 0 (forward) and 5 0 -GCTGAATCCTCCTTGACAAA-3 0 (reverse) for rat ITGAV, 5 0 -CGGACACACAACGTCTTGGAA-3 0 (forward) and 5 0 -AGGATGTA GGCGGTGGCTTTT-3 0 (reverse) for mouse c-Myc, 5 0 -GGGACA GTGTTCTCTGCCTCTGC-3 0 (forward) and 5 0 -AAGTTGCCACCGCC ACCGTCATC-3 0 (reverse) for rat c-Myc, 5 0 -AGGTCGGTGTGAACG GATTTG-3 0 (forward) and 5 0 -TGTAGACCATGTAGTTGAGGTCA-3 0 (reverse) for mouse glyceraldehyde-3-phosphate dehydrogenase, and 5 0 -GACATGCCGCCTGGAGAAAC-3 0 (forward), and 5 0 -AGCCCAG GATGCCCTTTAGT-3 0 (reverse) for rat glyceraldehyde-3-phosphate dehydrogenase.…”
Section: Quantitative Real-time Polymerase Chain Reactionmentioning
confidence: 99%
“…Cell proliferation was assessed by the BrdU assay as previously described. 47 Briefly, 10 mmol/l BrdU labeling solution was added to the culture medium, followed by incubation at 37 C for 4 hours. Then cells were fixed, denatured, and incubated with an anti-BrdU-POD (peroxidase) antibody for 90 minutes at room temperature.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%